This Time for Africa: African Conference on Experimental Archaeology (ACE) 2018 - Silje Evjenth Bentsen (EXARC, 2017)
Good news: The first African Conference on Experimental Archaeology (ACE) will be held in Johannesburg on the 20th to the 22nd of March 2018. Join us for presentations, posters, mini-workshops, demonstrations and round-table discussions of experiments in an African context!